Konstribusi Pesantren dalam Memfilter Modernisasi Sosial Budaya Masyarakat - Hassan, Muhammad N (LoroNG: Media Pengkajian Sosial Budaya, 2013)
Pesantren (Islamic boarding school) as religious educational institutions as well as community, was able to play its role as a renewal precursor. The existence of Islamic boarding school in fact willing to give alternative bids model of education, thought and action. This proved to be Islamic boarding school as the oldest educational institutions and survive amid the current transformation of socialcultural swiftly. Sociocultural alteration can be overcome with five elements. These elements are the elements that can form a Islamic boarding school, that Kiai (priest), mosque, dormitories, santri (student of Islamic boarding school), and kitab kuning (classical textbook). These elements have a function as sociocultural education in shaping behavior of sociocultural. Pesantren sebagai lembaga pendidikan keagamaan sekaligus kemasyarakatan, ternyata mampu memainkan peranannya sebagai pelo0(perubahan) sosial budaya masyarakat. Perubahan sosial budaya tersebut dapat diatasi dengan lima elemen. Elemen-elemen tersebut adalah unsur yang dapat membentuk pondok pesantren, yaitu kiai, masjid, asrama, santri, dan kitab kuning. Unsur-unsur yang membentuk pesantren tersebut berfungsi sebagai sarana pendidikan dalam membentuk perilaku sosial budaya masyarakat.